Ta'liq Divorce: The Procedure and Its Implementation in the Syariah Court of Shah Alam - Ainol Asni Binti Ahmad (2022)
This study is focused on the discussion on the procedures and its implementation of ta'liq divorce in Syariah Court of Shah Alam. The research is to explore the procedures and its implementation of ta'liq divorce in Syariah Court Shah Alam according with Islamic Family Law Enactment in Selangor 1984 and Selangor Syariah Enactment 1991. The research is library research and field study in Syariah Court of Shah Alam. The result from this study shows that the process to apply divorce under ta'liq must be based on the existing procedure as provided in the enactments to implement ta'liq, various procedures involved such as the judicial and administration process.